An ecological systems approach to understanding social support in foster family resilience. Issue 2 (21st September 2016) - Piel, Megan Hayes; Geiger, Jennifer M.; Julien‐Chinn, Francie J.; Lietz, Cynthia A.
Abstract: Families who care for children in the foster care system often experience challenges related to the system, accessing services and supports, and managing relationships. Despite these challenges, many families thrive because of unique attributes and strengths that contribute to experiences of resilience. Using an ecological framework, this study examined social support among resilient foster families to better understand how foster caregivers experienced positive reciprocal transactions across systems. As part of a larger study, in‐depth narrative interviews were conducted to examine the process of resilience for families who foster. Findings revealed that families accessed and benefited from social support on micro‐level, meso‐level and macro‐level. Understanding how families cultivated social support across multiple levels offers implications for practice and policy when considering how best to retain and support families who care for vulnerable children.